2020
DOI: 10.1186/s12935-020-01373-x
|View full text |Cite
|
Sign up to set email alerts
|

Genomic profiling of colorectal cancer with isolated lung metastasis

Abstract: Background: Metastasis is a major cause of failed colorectal cancer (CRC) treatment. While lung metastasis (LM) is observed in 10-15% of patients with CRC, the genetic mechanisms that cause CRC to metastasize to the lung remain unclear. Methods: In this study, we employed whole exome sequencing (WES) of primary CRC tumors and matched isolated LM lesions to compare their genomic profiles. Comprehensive genomic analyses of five freshly frozen primary tumor lesions, five paired LM lesions, and matched non-cancero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…By using tissue WES of primary CRC tumors and matched lung metastasis (LM), Zhang et al. 32 found primary and LM were founded by the same clone. However, Dang et al.…”
Section: Discussionmentioning
confidence: 99%
“…By using tissue WES of primary CRC tumors and matched lung metastasis (LM), Zhang et al. 32 found primary and LM were founded by the same clone. However, Dang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Isolated lung metastasis is more frequently reported in CRC patients than in those with other extrathoracic malignancies [ 5 , 11 , 12 ]. It is sometimes difficult to determine whether an SPN is PLC or an isolated lung metastasis because SPLC occasionally mimics isolated lung metastasis of CRC patients [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to CRLM, specific oncogenes are implicated in CRPM. Zhang et al [ 53 ] demonstrated through extensive genomic profiling studies of clinical samples from five CRC patients that CRPM shared clonality with primary tumors. Furthermore, 14 of 27 mutated genes identified in CRPM (i.e., KRAS , APC , and TP53 ) were also found in the primary lesion, thus suggesting that these mutations likely existed in the primary lesion itself.…”
Section: Colorectal Lung Metastasis (Crpm)mentioning
confidence: 99%
“…Furthermore, 14 of 27 mutated genes identified in CRPM (i.e., KRAS , APC , and TP53 ) were also found in the primary lesion, thus suggesting that these mutations likely existed in the primary lesion itself. As such, the identification of these mutations in the primary tumor during diagnostic workup or on post-resection pathologic analysis may be prognostically significant [ 53 ]. While surgical resection for isolated CRPMs is the only curative option for select patients, there are no high-quality clinical-trial data to guide practice.…”
Section: Colorectal Lung Metastasis (Crpm)mentioning
confidence: 99%